The Effect of Treatment with Mesenchymal Stem Cells on HbA1c and Insulin Requirement in Diabetic Patients: A Systematic Review and Meta-analysis - Parsa Eshragh Abad Shapori; Maryam Fathi (International Journal of Scientific Research in Dental and Medical Sciences)
Background and aim: This study explores the use of mesenchymal stem cells (MSCs) as a potential therapeutic option for diabetes treatment, addressing the increasing global prevalence of the condition, the lack of glucose control, the need for insulin injections, patient quality of life, and associated side effects. It investigates the impact of MSC treatment on HbA1c levels and insulin requirements in patients with diabetes. Material and methods: The present study included 13 RCT studies from international databases (PubMed, EMBASE, Web of Science, and Cochrane Library) up to April 30, 2025, identified using relevant keywords and based on study inclusion and exclusion criteria. The statistical analysis was performed using Stata/MP v17 as a fixed-effects model. Results: HbA1c levels in the group receiving MSC therapy were significantly lower than in the placebo group, with the mean changes of HbA1c being -0.72 (MD: -0.72; 95% CI, -0.95,-0.50). The mean changes of FPG in T1DM were -29.65 (MD: -29.65; 95% CI, -47.2, -12.28), and in T2DM were -0.68 (MD: -0.68; 95% CI, -1.56, -0.20). The test of group differences showed that the effectiveness of MSC therapy on both types of diabetes (T1DM and T2DM) in terms of C-peptide levels is similar (p = 0.08). Conclusions: A decrease in HbA1c levels, a decrease in fasting blood sugar, and an increase in C-peptide levels were observed after treatment with mesenchymal stem cells compared to the placebo group, indicating that mesenchymal stem cells can effectively affect the treatment process of diabetes.